2022
DOI: 10.1002/mop.33264
|View full text |Cite
|
Sign up to set email alerts
|

An ultra‐thin flexible four port MIMO antenna for WBAN communications

Abstract: This letter reports the design of a quasi Yagi‐Uda Antenna developed on an ultra‐thin flexible material for wireless body area networks (WBAN). The proposed planar Yagi‐Uda antenna operates at 2.45 GHz ISM band for medical applications. The microstrip line to slot line transition with circular geometry is used to obtain the necessary impedance matching. The proposed antenna has a footprint of 42 × 36 mm with a profile height of 0.05 mm. The quasi Yagi‐Uda antenna with a set of two directors exhibits 5% bandwid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…The reported antenna has the smallest footprint compared to Musa and colleagues 5,7,9,10,13,14 leading to a miniaturized solution. The percentage miniaturization realized by the proposed antenna compared to Musa and colleagues 5,7,9,10,13,14 are 20%, 46%, 87%, 19%, 48%, and 55%, respectively. 3.…”
Section: Diversity Analysismentioning
confidence: 94%
“…The reported antenna has the smallest footprint compared to Musa and colleagues 5,7,9,10,13,14 leading to a miniaturized solution. The percentage miniaturization realized by the proposed antenna compared to Musa and colleagues 5,7,9,10,13,14 are 20%, 46%, 87%, 19%, 48%, and 55%, respectively. 3.…”
Section: Diversity Analysismentioning
confidence: 94%
“…The WBAN applications become more common in healthcare, sports, military, space, and industrial applications, and therefore it becomes essential to develop flexible antennas facilitating the undisturbed use of these networks by the end users. Researchers have addressed this requirement from many different angles and have come up with different solutions [80], [81], [82], [83], [84], [85], [86], [87], [88], [89], [90], [91], [92], [93].…”
Section: Flexible and Wearable Antennamentioning
confidence: 99%
“…This antenna also showed that the resonance frequencies were slightly lowered when bent along either x-axis or y-axis, but still within the WBAN bandwidth for transmitting and receiving. Ramanujam and Perumalsamy reported a quasi Yagi-Uda antenna developed on flexible polyimide substrate operates at 2.45 GHz [85]. The designed antenna has dimensions of 42 × 36 mm and the thickness is 50 µm.…”
Section: Flexible and Wearable Antennamentioning
confidence: 99%
“…[13][14][15][16][17][18][19] Due to brevity, the discussions on those antennas are not included here. However, the research reported in Hasni and colleagues [13][14][15][16][17][18][19] signifies the importance of the chosen research domain and the challenges involved in meeting the technological requirements. In this paper, a metaheuristic algorithm named spider-monkey optimization is used in conjunction with the numerical solver CST microwave studio to design the dual-band wearable antenna targeted for IoT applications in the 2.45 and 3.4 GHz electromagnetic spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Some of interesting developments in wearable antennas have been demonstrated in Hasni and colleagues. [13][14][15][16][17][18][19] Due to brevity, the discussions on those antennas are not included here. However, the research reported in Hasni and colleagues [13][14][15][16][17][18][19] signifies the importance of the chosen research domain and the challenges involved in meeting the technological requirements.…”
Section: Introductionmentioning
confidence: 99%